Trend Fashion Masyarakat Indonesia saat Menghadiri Konser Musik K-Pop - Adrian, Regia Aulia Putri; Falah, Asep Miftahul (BAJU: Journal of Fashion and Textile Design Unesa, 2023)
A music concert is an event or performance held by musicians for music lovers as an appreciation for the music they create. Currently, Indonesian people are being inundated by music concerts held in various regions of Indonesia. Not only domestic musicians but also from abroad. Fashion is now an important part of watching music concerts. Not only as a music concert event but now the music concert event as a venue for art lovers to show their best fashion. Everyone has their own sense of fashion, so at the music concert event people wear a variety of fashions. From simple-looking fashion to fashions that look crazy-looking. The fashion trend of watching music concerts is now familiar, someone has their own concept when dressing up for a music concert. K-Pop or Korean Pop is a genre of music from South Korea, which is now widely loved by Indonesians from all walks of life. The enthusiasm of the Indonesian people to watch a music concert, especially a K-Pop music concert, is very high. The research method that will be used in this research is a qualitative method, distributing questionnaires to Indonesian people who like K-Pop music, by using the Phenomonology theory approach. Keywords: Fashion, Concert, Music, Indonesia, K-Pop.